Collaborative navigation field trials with different sensor platforms - Kealy, Allison; Retscher, Guenther; Hasnur-Rabiain, Azmir; Alam, Nima; Toth, Charles; Grejner-Brzezinska, Dorota A.; Moore, Terry; Hill, Chris; Gikas, Vassilis; Hide, Christopher D.; Danezis, Chris; Bonenberg, Lukasz Kosma; et al. (My University, 2013)
Collaborative (or cooperative) positioning or navigation uses multiple location sensors with different accuracy on different platforms for sharing of their absolute and relative localizations. Typical application scenarios are dismounted soldiers, swarms of UAV's, team of robots, emergency crews and first responders. This paper studies the challenges to realize a public and low-cost solution, based on mass users of multiple-sensor platforms. For the investigation field experiments revolved around the concept of collaborative navigation in a week at the University of Nottingham in May 2012. Different sensor platforms have been fitted with similar type of sensors, such as geodetic and low-cost high-sensitivity GNSS receivers, tactical grade IMU's, MEMS-based IMU's, miscellaneous sensors, including magnetometers, barometric pressure and step sensors, as well as image sensors, such as digital cameras and Flash LiDAR, and ultra-wide band (UWB) receivers. The employed platforms in the tests include a train on a building roof, mobile mapping vans and personal navigators. The presented preliminary results of the field experiments show that a positioning accuracy on the few meter level can be achieved for the navigation of the different platforms. © 2013 IEEE.
Keywords: Collaborative navigation; GNSS; INS; ubiquitous positioning